Gemstones from Roman Britain: Recorded in the Portable Antiquities Scheme - Henig, Martin (Acta Classica Universitatis Scientiarum Debreceniensis, 2024)
Roman gems have continued to be discovered in Roman Britain and published in archaeological reports and notes since the author completed his Corpus of Gems from British Sites in 1978. A new source of glyptic material can be found in the on-line publication of Portable Antiquities (Portable Antiquities Scheme) which includes intaglios, most of them found without stratigraphical context, by users of metal detectors, though many are set in rings, which provide significant aids in dating. Others were clearly re-used as they are set in seal matrices or medieval rings and were frequently freshly imported at that period from southern Europe. In the High Middle Ages, as in Roman times, intaglios reflect the interests, and patterns of thought of those who wore and valued these beautiful objects.